The Urgency of Registering Marriages In Jambi Province Based On The KHI of Maqāṣid Al-Syarīah Perspective - Taufik; Syukri, Ahmad; Bafadhal, Husin (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The aim of this research is to analyze specifically and in depth the urgency of registering marriages in Jambi Province based on the Compilation of Islamic Law from the Maqāṣid al-Syarīah perspective. The research method used is a type of qualitative research with the field research category. This research is also normative legal research, where the object can be public law, criminal law, civil law, family law, marriage law and so on. This research was conducted at the KUA in Jambi Province. The data sources in this research consist of primary and secondary data sources. The data collection techniques used in this research are observation, interviews and documentation. The results of this research show that marriage registration for the people of Jambi Province is very important. Based on the Maqāṣid al-Syarīah perspective, there is maṣlahah in registering marriages, namely to provide protection for the husband, wife and children in the family. If we pay attention to the legality of marriages in Indonesia, the state only recognizes registered marriages, on the basis of Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law.